Jordan : Request for an Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Jordan. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Jordan's Request for an extended arrangement under the Extended Fund Facility (EFF). The economic growth of Jordan remains below potential. Unemployment is high, particularly for youth and women, and the refugee crisis is weighing on the economy and public finances. Real GDP growth is projected to increase to 2.8 percent in 2016, supported by lower oil prices relative to their 2014 peak, an accommodative monetary stance, and some recovery in private investment. In view of Jordan's balance of payment needs, the policy actions already taken, and the comprehensive package of adjustment measures proposed by the authorities, the IMF staff supports the authorities' request for an extended arrangement under the EFF.